MENINGKATKAN KETERAMPILAN MELOMPAT MELALUI PERMAINAN TRADISIONAL LOMPAT TALI BAGI ANAK TUNAGRAHITA RINGAN KELAS II DI SDLB 35 PAINAN - Yusilia - Alfiza (Jurnal Penelitian Pendidikan Khusus, 2014)
This research was conducted based on the result of the previous observation indicating that the student with light mental retardation X got difficulties to do jumping. They seemed unable to jump forward, backward, to the right side and to the left side. Therefore, this research was intended to improve the students’ skill to do jumping through traditional game rope jump and to reveal whether this game could work on this problem. This was an experimental research which used Single Research Subject (SSR). In conducting this research, A and B designs were applied. The subject of the research was the students with light mental retardation X in class II of SDLB 35 Painan. The result of the research indicated that the skill of the students with light mental retardation X to jump forward, backward, to the right side and to the left side could be improved through traditional game rope jump. In the baseline condition (A) which consisted of seven meetings, the students were only able to jump forward for which the percentage was 25%. While in the intervention condition (B) that consisted of sixteen meetings, the students’ skill improved from the eighteenth meeting to the twentieth meeting in which the highest score was 100%.